Milk lactose protects against porcine group A rotavirus infection - Ren, Xiaolei; Saleem, Waqar; Haes, Robin; Xie, Jiexiong; Theuns, Sebastiaan; Nauwynck, Hans J. (Frontiers in Microbiology, 2022)
Rotavirus A (RVA) is an important pathogen causing acute gastroenteritis in animals and humans. Attachment to the host receptor is a crucial step for virus replication. The VP8* domain is the distal terminal region of the RVA spike protein VP4 (expressed by the P gene) and is important for rotavirus binding and infectivity. Recent studies have indicated a role for non-sialylated glycans, including mucin core 2 and histo-blood group antigens (HBGAs), in the infectivity of human and animal group A rotaviruses. In the present study, we determined if porcine rotavirus-derived recombinant VP8* of the endemic strains 14R103 G5P[6], 13R054 G5P[7], 12R010 G4P[13], 12R046 G9P[23], and 12R022 G2P[27] interact with hitherto uncharacterized glycans. We successfully produced five recombinant GST-VP8* proteins of genotype P[6], P[7], P[13], P[23], and P[27]. The hemagglutination assay showed genotypes P[7] and P[23] hemagglutinate porcine and human red blood cells. In an array screen of > 300 glycans, recombinant VP8* of rotavirus genotype P[6], P[7], and P[13] showed specific binding to glycans with a Gal-β-1,4-Glc (β-lactose) motif, which forms the core structure of HBGAs. The specificity of glycan-binding was confirmed through an ELISA-based oligosaccharide binding assay. Further, 13R054 G5P[7] and 12R046 G9P[23] infectivity was significantly reduced by β-lactose in MA104 cells and primary porcine enterocytes. These data suggest that lactose, the main natural sugar in milk, plays an important role in protecting piglets from enteric viral replication and diarrhea.